Pro kodifìkacìû trudovogo zakonodavstva v Ukraїnì ta problemi ї ї vìdpovìdnostì osnovnim položennâm nauki trudovogo prava - Pilipenko, Pilip (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The article is an analysis of the theoretical problems associated with the codification of labour law in Ukraine and the basic stages of preparing a draft of a new labour law — beginning with the development of its theoretical concept and ending with the adoption of the draft by the country’s legislative body. The author points to the broad spectrum of non-compliance of the main points of the draft Ukrainian Labour Code with the principles of labour law studies. This concerns both the validity of the normative act and the definition of the area to be regulated by law, as well as the explanation of basic terms employee, employer, contract of employment, employment relationship, etc..He also stresses the necessity of using international experiences in regulating hired labour, and proposes ways to improve certain points in the Code in order to strengthen the guarantees related to the employers’ and employees’ rights.
Keywords: Ukraina; prawo pracy; kodyfikacja ustawodawstwa pracy